Environmental Method to Determine Dopamine and Ascorbic Acid Simultaneously via Derivative Spectrophotometry - El-Zohry, Ahmed M.; Hashem, E. Y. (Journal of Spectroscopy, 2013)
Many various methods were applied to determine dopamine and ascorbic acid simultaneously using hazardous materials and complex procedures. Derivative absorption spectra can give safely and five sensitive derivative equations that are used for the simultaneous determination of dopamine and ascorbic acid in the UV region, using first and second derivative spectroscopy with high precision at pH value of 9.2. Dopamine and ascorbic acid can be detected in the ranges of 0.375–9.45 mg L−1 and 0.352–5.28 mg L−1, respectively. These obtained methods could be used to determine both reagents in real and synthesized samples.